ChemInform Abstract: Microwave Irradiated Synthesis of Some Substituted Imidazole Derivatives (IV) as Potential Antibacterial and Anticancer Agents. Issue 24 (23rd May 2013) - Sharma, Gyanendra Kumar; Sharma, Naveen Kumar; Pathak, Devender
Abstract All the new aryl‐substituted imidazole derivatives (IV) (10 examples) show good antibacterial activity against gram‐negative bacterial strains and significant cytotoxicity against DLA and EAC cell lines.